2004
DOI: 10.1046/j.1529-8817.2003.00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile Analysis in Human T Lymphocytes from Patients with Down Syndrome

Abstract: SummaryDown Syndrome (DS) is caused by the presence of three copies of the whole human chromosome 21 (HC21) or of a HC21 restricted region; the phenotype is likely to have originated from the altered expression of genes in the HC21. We apply the cDNA microarray method to the study of gene expression in human T lymphocytes with trisomy 21 in comparison to normal cells.Two patients with DS were investigated, along with two normal subjects as a control, all being tested in independent, duplicated cell culture exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Finally, this information can be used to discover new pathways of study on the pathophysiology of trisomy 21 and potential therapeutic intervention. Our microarray results are consistent with previous reports analyzing human trisomy 21 tissue or cells in that the overexpression of different chromosome 21 genes is cell type and developmental time specific [Gross et al, 2002;Mao et al, 2003;Lubec and Sohn, 2003;Giannone et al, 2004;Mao et al, 2005;Chung et al, 2005;Li et al, 2006;Ait Yahya-Graison et al, 2007;Rozovski et al, 2007]. Overexpression of chromosome 21 genes in our study is nonlinear ( 1 1.5-fold), again in agreement with previous reports [Lockstone et al, 2007].…”
Section: Microarray Analysis Reveals Changes In the Neural Progenitorsupporting
confidence: 83%
“…Finally, this information can be used to discover new pathways of study on the pathophysiology of trisomy 21 and potential therapeutic intervention. Our microarray results are consistent with previous reports analyzing human trisomy 21 tissue or cells in that the overexpression of different chromosome 21 genes is cell type and developmental time specific [Gross et al, 2002;Mao et al, 2003;Lubec and Sohn, 2003;Giannone et al, 2004;Mao et al, 2005;Chung et al, 2005;Li et al, 2006;Ait Yahya-Graison et al, 2007;Rozovski et al, 2007]. Overexpression of chromosome 21 genes in our study is nonlinear ( 1 1.5-fold), again in agreement with previous reports [Lockstone et al, 2007].…”
Section: Microarray Analysis Reveals Changes In the Neural Progenitorsupporting
confidence: 83%
“…Earlier studies suggested a great variation in the oxidative metabolic potential of immune cells in Down syndrome individuals, and a more recent and notable observation provides a new clue to the relationship between Down syndrome and the immune system. The gene expression profile analysis in T-lymphocytes from two patients with Down syndrome showed over-expression of the superoxide dismutase (SOD) gene which is located on trisomic chromosome 21q.16 [77]. SOD is a key enzyme in the metabolism of oxygen-derived superoxide (O 2 À ) to hydrogen peroxide (H 2 O 2 ) and SOD activity is increased in various tissues in Down syndrome [78][79][80].…”
Section: Systemic Immunodeficiencymentioning
confidence: 99%
“…Previous reports analyzing human trisomy 21 tissue or cells have shown that overexpression of different chromosome 21 genes is cell type and developmental time specific (Ait Yahya-Graison et al, 2007;Chung et al, 2005;Giannone et al, 2004;Gross et al, 2002;Li et al, 2006;Lubec and Sohn, 2003;Mao et al, 2005;Mao et al, 2003;Rozovski et al, 2007). For example, by RNA whole-mount in situ hybridization, gene expression maps of HSA21 orthologues in various aged embryonic or newborn mouse brain have been reported (Gitton et al, 2002;Reymond et al, 2002).…”
Section: Temporal-spatial Mapping-based Clustersmentioning
confidence: 99%